Pengembangan LKM STEM dengan Arduino Uno Sensor PH-4502C Materi Bioteknologi untuk Meningkatkan Berpikir Kreatif Mahasiswa - Mei Kurniasari; Pramita Yakub; Rinie Pratiwi Puspitawati (Biosfer: Jurnal Pendidikan Biologi, 2026)
This study aims to develop STEM-based student worksheet on environmental biotechnology material and analyze their validity, practicality, and effectiveness in improving students' creative thinking skills. This study uses the 4D model development method, which includes the define, design, develop, and disseminate stages, with 40 students from the Biology Study Program at Surabaya State University class of 2025 as the research subjects. The research instruments included expert validation sheets, student response questionnaires, activity observation sheets, and pretest and posttest tests of creative thinking skills. The data were analyzed using validity and practicality percentages and N-Gain scores to measure effectiveness. The results showed that the STEM-based student worksheet were highly valid with a validity percentage above 85% and highly practical based on student responses. The readability level was appropriate for students. The effectiveness of the student worksheet was demonstrated by an increase in the average creative thinking ability score from 68.75 on the pretest to 95.00 on the posttest with N-Gain values in the high to very high category. These findings indicate that the integration of the STEM approach through experimental activities and the use of technology is effective in training student creativity. This study recommends the use of STEM-based student worksheet as innovative teaching materials to support biotechnology learning in higher education.